Environmental microbiology : - Madsen, Eugene L. (Blackwell, 2008)
Over the past 20 years, environmental microbiology has grown from relative obscurity into a vibrant area of both pure and applied science. Environmental microbiology is inherently multidisciplinary-relying upon contributions from analytical chemistry, geosciences, environmental engineering, public health, ecology, evolution and microbiology. How is it possible to meet the challenge of integrating these disciplines so that students emerge with knowledge, competence, and enthusiasm?This well-referenced resource is filled with ideas, connections, and concepts that advance an in-depth understanding of this growing segment of biology. Core principles are highlighted with an emphasis on the logic of the science and new, methods-driven discoveries. Numerous up-to-date examples and applications boxes provide tangible reinforcement of material covered. Study questions at the end of each chapter require students to utilize analytical and quantitative approaches, to define and defend arguments, and to apply microbiological paradigms to their personal interests. Essay assignments and related readings stimulate student inquiry and serve as focal points for teachers to launch classroom discussions.Environmental Microbiology: from genomes to biogeochemistry offers a coherent and comprehensive treatment of this dynamic, emerging field - building bridges between basic biology, ecology, and the environmental sciences